The Use of Nearpod Interactive Media in Science Subjects in Elementary Schools - Adib Muzakki; Wuri Wuryandani; Sekar Purbarini Kawuryan (Jurnal Penelitian Pendidikan IPA, 2025)
This study uses a literature study method or Systematic Literature Review (SLR) which examines the use of Nearpod interactive media in the subject of science in elementary schools. This study aims to provide information related to the use of Nearpod interactive media in the subject of science in elementary schools in supporting the learning process in the classroom. The method used is a literature study where the data used is data from various sources, such as journals, books, scientific papers, and other libraries. The collection of data is analyzed one by one to be grouped and combined into a complete conclusion. The results of the study show that the use of Nearpod interactive media in the subject of science in elementary schools greatly supports the learning process, Nearpod has proven effective in improving students' understanding of concepts, strengthening mastery of material better than conventional methods. In addition, Nearpod not only supports students' cognitive aspects, but also makes it easier for teachers to design more interactive and structured learning. Therefore, Nearpod is an alternative digital learning media that is very potential to be applied in science learning in elementary schools.